Economic development as a way to fight against poverty in a coastal society - Rukin Rukin (Masyarakat, Kebudayaan dan Politik, 2018)
This research is based on the phenomenon of low construction in coastal village areas, primarily in relation to the economic development sector. This study was conducted in order to determine the low economic level of coastal rural communities and its abundant natural resources (SDA). The government has already issued a public policy related to economic empowerment and coastal zone management. However, the coastal village community’s economy remains very low. The qualitative and phenomenological approach was used to obtain the findings about why society in coastal villages is economically low level. The main cause of the economic problem was the lack of ability of the public to capture the business opportunities that existed. In addition, the constant hereditary lifestyle of the coastal people is one of the triggers of their low economic power. There is a lack of distinct empowerment by the government in order to improve their economy. SDA has not been optimally empowering coastal areas by way of the village communities of the coast and there is a lack of village infrastructure. The concrete participation of the local government is expected in relation to the handling of economic empowerment. One solution that can be undertaken is the revamping of public policy related to the development of coastal villages. The completion of the installation program for paving and street lighting is also a priority. The development and empowerment of the economy should be done immediately. Another thing that can be done by the government is the optimisation of the religious and beach tourism there.